Granulosis Rubra Nasi: A Case Report and Brief Review of the Literature - Girum T. Assefa (Case Reports in Dermatological Medicine, 2023)
Granulosis rubra nasi is a rare autosomal dominant disease of the eccrine glands. It is clinically characterized by mid-face hyperhidrosis, most prominent at the tip of the nose, and dark erythematous papules on the nose, cheeks, chin, and upper lip. Although it commonly occurs in childhood, it can also occur in adults. This is a case report of two female granulosis rubra nasi patients. This report, to the best of my knowledge, has not before been described in Ethiopian individuals and is hence being reported due to its rarity.